2020
DOI: 10.2147/ott.s227395
|View full text |Cite
|
Sign up to set email alerts
|

<p>DNMT1 Enhances the Radiosensitivity of HPV-Positive Head and Neck Squamous Cell Carcinomas via Downregulating SMG1</p>

Abstract: Introduction: Head and neck squamous cell carcinoma (HNSCC), which rank the 7th malignant tumors worldwide, is closely related to methylation and HPV infection. Ionizing radiation therapy is the main strategy for HNSCC patients in advanced stage. Previously, HPV-positive HNSCC predict better prognosis than HPV-negative HNSCCs under radiotherapy, however its molecular mechanism is unresolved. SMG1 serves as a potential tumor suppressor in various cancers, including HNSCC. Methods: The mRNAs and proteins express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Besides, there was a strong correlation between DGCR8 and hsa-miR-106a (Figure 2). As we have known in previous studies (22), HPV-positive HNSCC cells were highly sensitive to radiation, and HPV-positive cells were rich in DGCR8 and hsa-miR-106a. Ardenne and Reitnauer (27) demonstrated that hsa-miR-106a suppressed proliferation and induced apoptosis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Besides, there was a strong correlation between DGCR8 and hsa-miR-106a (Figure 2). As we have known in previous studies (22), HPV-positive HNSCC cells were highly sensitive to radiation, and HPV-positive cells were rich in DGCR8 and hsa-miR-106a. Ardenne and Reitnauer (27) demonstrated that hsa-miR-106a suppressed proliferation and induced apoptosis.…”
Section: Discussionsupporting
confidence: 56%
“…According to previous studies, we had proved that FaDu and UM-SCC-4 were HPV-negative cell lines and do not express HPV E7 proteins, while UM-SCC-090 and UM-SCC-47 were HPV-positive cell lines expressing E7 proteins (22). The mRNA ( Figure 1A) and protein ( Figure 1B) expressions of E7 in HPV-positive cell lines were higher than those of HPV-negative cell lines.…”
Section: Human Papillomavirus E7 Upregulates Dgcr8 Expression In Headmentioning
confidence: 70%
“…DNMTs may be a potential target for enhancing HNSCC chemotherapy by using inhibitors of DNMTs and reversal of gene methylation [ 51 , 52 ]. It has been reported that DNMT1 enhances the radiosensitivity of neck squamous cell carcinomas via downregulating SMG1 [ 53 ]. The zinc finger protein 318 (encoded by the ZNF318 gene) was recognized previously as a blood pressure regulator [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the levels of DNMT3B, NSUN2, DNMT3A, NOP2, DNMT1, NSUN4, NSUN5, and ALYREF were upregulated in lung adenocarcinoma (52). Zhang et al (53) have found that DNMT1 could enhance the radiosensitivity of HPV-positive HNSCC through suppressor of morphogenesis in genitalia 1 (SMG1). The NSUN family member, NSUN2, is found to be implicated in regulating cell cycles and accumulates in a variety of tumor lesions compared with normal samples (25,54).…”
Section: Discussionmentioning
confidence: 99%